Differentiation and Temperature Adaptation of Pampus Echinogaster Based on Genome-Wide SNPs - Li, Yuan; Lou, Fangrui; Liu, Shigang; Li, Hai; Xiang, Jiali; Shan, Binbin; Lin, Longshan; Zhuang, Xuan (Frontiers in Marine Science, 2022)
Climate change and overfishing have led to the degradation of the quality and stock of Pampus echinogaster. Exploring the genetic structure and local adaptive evolutionary mechanisms of P. echinogaster is crucial for the management of this species. This population genomic study of nine geographical populations of P. echinogaster in China was conducted by specific-locus amplified fragment sequencing (SLAF-seq). A total of 935,215 SLAF tags were obtained, and the average sequencing depth of the SLAF tags was 20.80×. After filtering, a total of 46,187 high-consistency genome-wide single nucleotide polymorphisms (SNPs) were detected. Based on all SNPs, the population size of the nine P. echinogaster geographical populations was large. The Shantou population had the lowest genetic diversity, and the Tianjin population had the highest. Moreover, the population genetic structure based on all SNPs revealed significant gene exchange and no significant genetic differentiation among the nine P. echinogaster geographical populations, probably because of the population expansion after the last glacial period, the lack of balance between migration and genetic drift, and the long-distance diffusion of eggs and larvae. We suspect that variation of material metabolism, ion transfer, breeding, stress response, and inflammatory reactions-related genes were critical for adaptation to spatially heterogeneous temperature selection in natural P. echinogaster populations.